Sociology 571 - Sociology of the Life Course: Final Examination - Carr, Deborah (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
Instructions: You must provide answers to three of the following four questions. Be sure to answer each part of the questions you’ve selected. Your answers must incorporate information provided in required readings and in lecture. You may also feel free to draw on recommended readings as well as articles you have read for other classes and as part of your own research. You should limit each answer to roughly five pages of double-spaced type. You will deliver a hard copy of your exam to my LSH mailbox by 5 p.m. on Monday, May 12. E-mail attachments will not be accepted. (It is recommended that this examination be used with Sociology 571 Syllabus by Deborah Carr).